2020
DOI: 10.1111/jce.14723
|View full text |Cite
|
Sign up to set email alerts
|

Esophago‐pericardial fistula after catheter ablation of atrial fibrillation: A review

Abstract: Introduction: Much have been reported about esophago-left atrium fistula. However, esophago-mediastinal fistula, not reaching the left atrium, has not been studied as a different clinical entity, with different management. Methods and Results: We review and discuss the literature of esophagomediastinum fistula after catheter ablation for atrial fibrillation with emphasis on the following points: the timing of its occurrence after ablation; the mechanisms and localization of the fistula; and its natural history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A cascade of events, including direct thermal injury, infection, and local ischemia, seem to be involved, ultimately leading to ulceration and fistula formation, 17 although the exact mechanisms of injury, the physiopathology of progression to fistula, and best management have not yet been completely mastered, mainly because of its low incidence (0.1%–0.2%) 18–20 . Routine post‐procedural endoscopy can be adopted as an effective strategy for early detection, except for rare descriptions of AEF cases preceded by a normal‐appearing mucosa soon after ablation 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cascade of events, including direct thermal injury, infection, and local ischemia, seem to be involved, ultimately leading to ulceration and fistula formation, 17 although the exact mechanisms of injury, the physiopathology of progression to fistula, and best management have not yet been completely mastered, mainly because of its low incidence (0.1%–0.2%) 18–20 . Routine post‐procedural endoscopy can be adopted as an effective strategy for early detection, except for rare descriptions of AEF cases preceded by a normal‐appearing mucosa soon after ablation 21 …”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of early diagnosis, routine endoscopy should be encouraged. Worsening deep ulcers and FAE AEF at early stages have been approached with esophageal stenting and surgical repair, still with elevated mortality rates 18–21 . Endoscopic negative pressure therapy has proved its efficacy for non‐thermal esophageal acute lesions, 27‐29 with primary success rates varying from 70% to 100%, low cost, and no adverse events 4,5 .…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Esophageal stents, however, still have a role in the management of esophagopericardial fistulas. A recent review of esophagopericardial fistulas by Sternick and colleagues 24 found that stenting in this situation with esophagomediastinal or pericardial fistulas (without breaching into the left atrium) had a favorable outcome. Either percutaneous or thoracotomy approaches to mediastinal, pleural, and pericardial drainage have been applied in these cases as part of the procedure.…”
Section: Treatment Approachesmentioning
confidence: 99%
“…In reported case series of AEF, approximately 10% account for EPF cases, and mortality is relevantly lower. In published reports, patients in 33 of 39 reported and summarized cases survived (85%), usually without major sequelae, and management ranged from broad-spectrum antibiotics alone to adding esophageal stenting in combination with pericardial drainage or complex surgical procedures ( 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ).…”
Section: Management Of Esophagopericardial Fistulamentioning
confidence: 99%
“…It is unclear if EPF is an early form of esophageal perforating complications that may progress to AEF or why in some of these cases fistulation stops before entering the left atrium. In an interesting report by James ( 10 ) on cases of pneumopericardium stemming from esophageal perforating injuries (mostly from foreign body ingestions) no case of perforation into the left atrium was observed implying that the mechanism of AEF may also involve a “locus minoris resistentiae” of the left atrial wall (probably induced by the AF ablation ( 9 ). Therefore, the most obvious difference to AEF is the lack of neurological complications in EPF, a known factor of poor prognosis in AEF cases ( 2 , 3 , 4 , 5 ).…”
Section: Differences Between Esophagopericardial Fistula and Esophagoatrial Fistulamentioning
confidence: 99%